Komorbidity Mapping of COVID-19 Events in West Sumatera - Yuniarti, Elsa; Indika, Pudia M; Dewata, Indang; Heldi, Heldi; Barlian, Eri (Sumatra Journal of Disaster, Geography and Geography Education, 2020)
West Sumatra as one of the provinces in Indonesia affected by COVID-19 is among the 10 highest case provinces. West Sumatra also has a high comorbidity rate. Distribution of comorbid cases (elderly, hypertension and diabetes mellitus) are found in all districts / cities in West Sumatra. The aim of the study was to map the distribution of comorbid populations against COVID-19 events in West Sumatra. This type of research is quantitative descriptive. A systematic data search carried out by the comorbid population against COVID-19 was obtained from the health profile database of the health department, West Sumatra Central Statistics Agency 2018, and https://corona.sumbarprov.go.id/ to update the latest case of COVID-19 by Regency / City in West Sumater Province. The distribution of comorbidity is carried out using GIS analysis techniques using Arc-GIS 10.5 software. The highest incidence of COVID-19 and the highest comorbid population in West Sumatra is found in Padang City as the epicenter of spread. Data in the city of Padang are 65,550 elderly, hypertension 203,787 and diabetes mellitus 22,538 and 177 cases of COVID-19 positive confirmed. The conclusion is the high number of comorbid people makes Padang City a high-risk area for COVID-19 in West Sumatra Province.